Una mirada historica de la relación del estado nación chileno con los pueblos originarios. - Cáceres, Jorge (My University, 2019)
Chile has developed historically from the cultural homogeneity, marginalizing the indigenous people, and popular groups of social and cultural life. As of the nineteenth century, Chile is constituted as a modern State, creating for it a strong and solid uniform identity that characterizes us as a nation in order to achieve development. The two centuries of independent life have reaffirmed the idea of uniformity under a political discourse which does not recognize cultural diversity. This work shows the relationship between the Chilean State and the conflicts that have arisen therefrom.
Chile se ha desarrollado históricamente desde la homogeneidad cultural, marginando a indígenas y a grupos populares de la vida social y cultural y que a partir del siglo XIX, se constituye como un Estado moderno, creando para ello una férrea y sólida identidad uniforme que nos caracterice como nación para sí alcanzar el desarrollo. Los dos siglos de vida independiente han reafirmado la idea de uniformidad bajo un discurso político que no reconoce la diversidad cultural y, en este trabajo, exponemos la relación del Estado chileno y los conflictos que se han generado.
Keywords: ESTADO HOMOGÉNEO; IDENTIDAD CULTURAL; DIVERSIDAD CULTURAL; CONFLICTO